Determination of expandability clay from San José de Cucuta metropolitan area, by varying calcination temperature and time (2019)
In this article, the volumetric change of the clay granules and sewage sludge (technological nutrient), San José de Cúcuta metropolitan area raw materials, when calcined at different temperatures and different burning times is shown. The main objective is to evaluate out the work right conditions (temperature and time), for the production of light aggregates from expanded clay. The methodology that was followed consists of three phases: preparation and pelletization of clay mixtures and technological nutrient; application of heat treatment in a set of muffle furnaces; and application of statistical treatment with the help of Software R. One of the most important results is that the expansion of the clay is indifferent to the time it takes to cook the pellets, and that this property depends solely on the temperature of burning. The temperature that generates the greatest expansion is 1,200 Celsius degrees, using a set of muffle furnaces.